THE EFFECTIVENESS OF PROJECT-BASED LEARNING IN IMPROVING ORAL COMUNICATION SKILLS IN ENGLISH - Rivaldo R. Tina; Magvirah El Walidayni Kau; Haris Danial (Review of International Journal Education and School Leadership, 2025)
This study analyzes the aspects of Project-Based Learning (PjBL) effectiveness in improving students’ oral communication skills in the English Language Education Study Program (ELESP) at Universitas Negeri Gorontalo. It specifically aims to identify which aspects of PjBL are most effective in improving students’ oral proficiency in oral communication skills in ELESP at Universitas Negeri Gorontalo. This research employed a descriptive qualitative method, and data were collected through classroom observations and interviews with five students and one lecturer. The classroom observations were analyzed based on the six phases of the PjBL syntax, while interview data were coded using indicators of oral communication, including verbal elements, paralinguistic features, and non-verbal cues. The combined analysis revealed three major aspects contributing to PjBL’s effectiveness: (1) Student Engagement and Active Participation, (2) Challenges in Target Language Usage, and (3) Communication Skills Development. The findings demonstrate that consistent and structured PjBL implementation improves students’ language use, collaboration, confidence, and interactive communication. The study concludes that PjBL is an effective instructional approach for developing oral communication skills in professional and academic contexts.